2015
DOI: 10.1016/j.stemcr.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Macular Degeneration Using Embryonic Stem Cell-Derived Retinal Pigment Epithelium: Preliminary Results in Asian Patients

Abstract: SummaryEmbryonic stem cells hold great promise for various diseases because of their unlimited capacity for self-renewal and ability to differentiate into any cell type in the body. However, despite over 3 decades of research, there have been no reports on the safety and potential efficacy of pluripotent stem cell progeny in Asian patients with any disease. Here, we report the safety and tolerability of subretinal transplantation of human embryonic-stem-cell (hESC)-derived retinal pigment epithelium in four As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
238
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(253 citation statements)
references
References 31 publications
8
238
1
6
Order By: Relevance
“…The latter trial recently reported 12-month follow-up data from four patients that show no adverse effects and improved visual acuity following RPE transplantation, supporting the findings of Schwartz et al, 2015(Song et al, 2015.…”
Section: Box 1 the Regulatory Path From The Lab To The Clinicmentioning
confidence: 53%
“…The latter trial recently reported 12-month follow-up data from four patients that show no adverse effects and improved visual acuity following RPE transplantation, supporting the findings of Schwartz et al, 2015(Song et al, 2015.…”
Section: Box 1 the Regulatory Path From The Lab To The Clinicmentioning
confidence: 53%
“…Overall, this speaks to the need to deliver the RPE monolayer on an artificial membrane, as is being proposed by both ourselves (figure 1), and others [22]. Despite these data, delivery of RPE as a cell suspension has been the approach taken by Advanced Cell Technology [5], and Cell Cure Neurosciences (https://clinicaltrials.gov/ct2/ show/NCT02286089?term=opregen&rank=1).…”
Section: Why Start With the Eye?mentioning
confidence: 86%
“…Human ESCsderived retinal pigment epithelium was used to treat age-related macular degeneration and Stargardt's macular dystrophy (Schwartz et al, 2015) in Phase I/II ( Table 7). Preliminary results after 1 year of treatment showed that visual acuity improved (9-19 letters in three patients) and remained stable (+1 letter in one patient) (Song et al, 2015). Besides, ESCs and iPSCs were also used to treat other diseases such as spinal cord injury, geographic atrophy secondary to myopic macular degeneration, Stargardt macular degeneration of retina, dry macular degeneration of retina, wet macular degeneration of retina, diabetes Type I, heart failure, and immunotherapy vaccine for lung cancer.…”
Section: Embryonic Stem Cells and Induced Pluripotent Stem Cellsmentioning
confidence: 94%